2020
DOI: 10.1101/2020.05.27.20115030
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physical violence during pregnancy in Peru: Proportion, geographical distribution, and associated factors

Abstract: Objective: Estimate the proportion, geographic distribution and sociodemographic factors associated with physical violence during pregnancy between 2016 and 2018. Material and methods: Secondary analysis of the Demographic and Family Health Survey, which included respondents whether they presented physical violence during pregnancy in the last 12 months. Results: The proportion of physical violence was 9,9% [95%CI:9,6-10,4%] during 2016, 9,2% [95%CI:8,8-9,6%] during 2017 and 8,6% [95%CI:8,3-8,9%] during 2018, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…Another study conducted in Tanzania showed the same association (aOR = 3.20; 95% CI: 1.30-7.70) [15]. The evidence on the association between physical violence during pregnancy and this type of outcome is rare in Latin American countries, such as Peru, in which 1 in 10 pregnant women suffers physical violence [3].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Another study conducted in Tanzania showed the same association (aOR = 3.20; 95% CI: 1.30-7.70) [15]. The evidence on the association between physical violence during pregnancy and this type of outcome is rare in Latin American countries, such as Peru, in which 1 in 10 pregnant women suffers physical violence [3].…”
Section: Introductionmentioning
confidence: 90%
“…Similarly, the prevalence was highest in Oceania (19.1%) and Africa (16.3%), followed by South America (9.8%) [2]. In Peru, the prevalence of physical violence in pregnant women in 2019 was estimated at 8.6% [3]. In this regard, physical violence during pregnancy could affect the mother indirectly through the development of depression, anxiety, drug abuse, and alcoholism, as well as directly due to possible abdominal damage and placental abruption [1].…”
Section: Introductionmentioning
confidence: 99%
“…De manera similar, la prevalencia fue más alta en Oceanía (19,1 %) y África (16,3 %), seguida de América del Sur (9,8%) (2). En Perú, la prevalencia de violencia física en gestantes se estimó en 8,6% en 2019 (3). En este sentido, la violencia física durante el embarazo podría afectar a la madre indirectamente a través del desarrollo de depresión, ansiedad, abuso de drogas y alcoholismo, así como directamente debido a un posible daño abdominal y desprendimiento de placenta (1).…”
Section: Introductionunclassified